2015
DOI: 10.1186/s13104-015-1750-3
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and the risk of cardiovascular disease among workers in cocoa processing company, Tema

Abstract: ObjectiveShift work has been implicated in cardiovascular disease (CVD), a major cause of death globally. The aim of this study was to evaluate the risk of developing CVD in shift work.DesignA cross-sectional study involving secondary analysis of shift and non-shift work from an industry in Ghana.ParticipantsTwo hundred (113 shift and 87 non-shift) consecutive workers who consented were recruited into the study. A structured questionnaire was administered to deduce information on participant’s age, alcohol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
20
0
6
Order By: Relevance
“…In our study, blood pressure was higher than 139/89 mmHg in one in four workers, with hypertension significantly more frequent among men aged 41-50 (31.9%). In the other studies, elevated cholesterol levels among shift workers were observed and an elevated triglyceride level was reported to be associated with shift work [2,13]. This may be due to reduced sleep duration associated with the shift work.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In our study, blood pressure was higher than 139/89 mmHg in one in four workers, with hypertension significantly more frequent among men aged 41-50 (31.9%). In the other studies, elevated cholesterol levels among shift workers were observed and an elevated triglyceride level was reported to be associated with shift work [2,13]. This may be due to reduced sleep duration associated with the shift work.…”
Section: Discussionmentioning
confidence: 86%
“…This observation could be due to more stressful jobs being given to the younger workers and leaving the less stressful jobs for the older workers. Continued shift work could also lead to adaptation of biological rhythms that do not promote hypertension [2]. It has been reported that shift work is associated with an increased prevalence of hypertension, but data are inconclusive [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Estudo mostra que trabalhadores do turno apresentam prevalência mais alta de fatores de risco para doenças cardiovasculares, como aumento da glicemia, aumento da pressão arterial, perfis lipídicos alterados e obesidade, quando comparados aos trabalhadores do turno diurno. 12 O trabalho em turnos inclui qualquer arranjo do horário de trabalho diário além das horas diurnas padrão (7h/8h-17h/18h), tais como turnos noturnos e alternantes (turnos de trabalho em horários alternados). 13 No turno alternante, os trabalhadores se revezam trabalhando em todos os turnos de um sistema específico de jornada de trabalho.…”
Section: Introductionunclassified